2013
DOI: 10.1136/heartjnl-2012-302949
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial progenitor cells, atheroma burden and clinical outcome in patients with coronary artery disease

Abstract: Traditional EPC populations, CD34(+)VEGFR-2(+) and CD34(+)VEGFR-2(+)CD133(+) are not related to the extent of CAD or clinical outcome. However, CD34(+)CD45(-) cells are increased in patients with CAD and predict future cardiovascular events. It is likely that CD34(+)CD45(-) concentrations reflect the extent of vascular injury and atheroma burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 29 publications
3
26
1
Order By: Relevance
“…Concerning the investigated populations of putative EPC and CEC, all subgroups have been quantified in similar patient populations [7,[27][28][29]. Compared with these reports, our EPC and CEC numbers were highly similar.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Concerning the investigated populations of putative EPC and CEC, all subgroups have been quantified in similar patient populations [7,[27][28][29]. Compared with these reports, our EPC and CEC numbers were highly similar.…”
Section: Discussionsupporting
confidence: 72%
“…Yet, another group has reported no increase of CD34 + cells after implantation of sirolimus-eluting stents measuring at various time points up to one month [35]. Thus, our model of assessing strut coverage 6 months after stent implantation should well reflect the influence of EPC on late vascular healing as it has been proposed more recently [28]. Early analysis of stent strut coverage in patients with acute coronary syndromes might represent an alternative to assess the effects of high CEC or EPC levels, yet the presence of thrombotic material may hinder identification of true endothelium [12,14].…”
Section: Limitations Of the Studymentioning
confidence: 83%
See 1 more Smart Citation
“…The authors agree with Padfield G. J. et al . [15] who showed that CD34 + CD45 − cell number was increased in patients with CAD compared with those with normal coronary arteries and correlated well with atheroma. The authors believed that CD14 + VEGFR-2 + Tie-2 + cells and endothelial cell-colony forming units were increased in patients with acute coronary syndrome; that cell concentrations reflected myocardial necrosis, and did not predict the extent of CAD.…”
Section: Resultsmentioning
confidence: 99%
“…Basically, CD34 + CD45 − cells have nonhematopoietic origin; and recently they have been identified as putative EPCs by virtue of their ability to form “late outgrowth” colonies phenotypically and functionally indistinguishable from mature endothelial cell colonies in culture [12,13]. Previous studies have shown an increase in the circulating concentration of population CD34 + CD45 − cells in patients with established coronary artery disease (CAD) and peripheral artery disease [10,14,15]. Theoretically, CD34 + cells which do not express CD45 by flow cytometry may include cells capable of developing bona fide endothelial cells.…”
Section: Introductionmentioning
confidence: 99%